2010
DOI: 10.1086/655660
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Serological Responses of Adults toHelicobacter pyloriAntigens

Abstract: Since Helicobacter pylori persist for decades in the human stomach, the aim of this study was to examine the long-term course in H. pylori-specific serum IgG responses with respect to subclass and antigenic target. We studied paired serum samples obtained in 1973 and in 1994 in Vammala, Finland from 64 healthy H. pylori-positive adults and from other healthy controls. H. pylori serum IgA, IgG, and IgG subclass responses were determined by antigen-specific ELISAs. H. pylori-specific IgG1 and IgG4 subtype respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Studies on switch class variants for both malaria and other infectious pathogens have found that antibody affinity and avidity will differ between antigens of the same pathogen or even between different domains of a single antigen [ 39 , 40 ]. This can be due to factors such as age and gender, antigen density, strain of the organism, and epitope specificity [ 38 , 41 , 42 ]. Ultimately, current evidence on the associations of antigen-specific IgG subclasses with both exposure and immunity to malaria is varied [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on switch class variants for both malaria and other infectious pathogens have found that antibody affinity and avidity will differ between antigens of the same pathogen or even between different domains of a single antigen [ 39 , 40 ]. This can be due to factors such as age and gender, antigen density, strain of the organism, and epitope specificity [ 38 , 41 , 42 ]. Ultimately, current evidence on the associations of antigen-specific IgG subclasses with both exposure and immunity to malaria is varied [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we have no knowledge of whether H pylori may have been lost or gained in the interval between ascertainment and mortality. However, from longitudinal studies of H pylori- positive adults, we know that rates of ‘spontaneous’ annual loss of the organism among those with established colonisation are low 29. Similarly, early childhood is the nearly exclusive time for colonisation,24 25 thus substantial later-in-life acquisitions are unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori gives rise to a systemic and stable IgG antibody response [25], which only decreases after bacterial eradication by antibiotic treatment or by development of atrophic gastritis. In a previous study by our group, the same ELISA test was used to determine the prevalence of H. pylori in 6‐ to 8‐year‐old Dutch children in 1978 and 1993 [10], showing a marked (52%) decrease in H. pylori prevalence between 1978 and 1993.…”
Section: Discussionmentioning
confidence: 99%